Kajian Semiotik Ornamen Interior Pada Lamin Dayak Kenyah ( Studi Kasus Interior Lamin Di Desa Budaya Pampang) - M Taufan Rizqy, Maria Sicilia Mayasari Lintu Tulistyantoro (Intra, 2014)
The carvings and ornaments in Dayak Kenyahâs Lamin in the Pampang village have many signs that filled with meaning that is interesting to be explored. These signs serve as a representation of their beliefs and their social life. This study aims to reveal the meaning of these signs from the point of view of Peircean semiotics. Steps used in analyzing these signs is to group them into categories of icon, index, and symbol, then combined with the analysis of the meaning of denotation, connotation, and social aspects. The results of the analysis showed that the signs contained in this Lamin convey meaning, not only with regard to their confidence in the magic but also has a meaning related to social aspects.